A method for pretreatment of ion membrane in flow battery
Through the primary and secondary treatment of the liquid stream battery ion membrane, the selectivity and swelling rate are improved, the difficulty and reliability of the electric heap assembly caused by the inflation of ion membranes in the existing technology, and improving the battery's charging and discharge efficiency And cycle stability.
Patent Information
- Application Number
- CN202210697592.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-06-20
AI Technical Summary
In the prior art, ionic membranes swell after contact with water or solution, resulting in changes in membrane size, increasing the difficulty of stack assembly, reducing stack reliability, and poor vanadium resistance performance, resulting in battery capacity loss and low Coulomb efficiency.
A pre-processing method of liquid-flowing battery ion membrane, including the initial treatment of ion membranes in sugar solutions such as D-glucosamate acid, and then conducting secondary treatment in the alkaline metal ion neutral solution, the flat exhibition of the control membrane controls the membrane Status to ensure its stability during the processing process.
Through this method, the selectivity and swelling rate of ion membranes have been significantly improved, the efficiency and cycle stability of the battery have also improved, reducing the risk of internal leakage of the electric heaps caused by the inflation of ion membranes, and extending the service life of the battery life. Essence
Smart Images

Figure BDA0003703308590000051 
Figure BDA0003703308590000091 
Figure BDA0003703308590000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of all-vanadium liquid flow batteries, and in particular relates to a method for pretreating an ion membrane of a liquid flow battery. Background Art
[0002] As one of the key materials of all-vanadium liquid flow batteries, the performance of ion exchange membrane directly affects the performance and service life of the battery. Ion membrane is used to separate the positive and negative electrodes of the battery into two discontinuous phases, construct the internal conductive circuit of the battery and allow specific ions to selectively permeate. Since dry ion membrane will absorb water and swell after being wetted, wet membrane assembly is usually used during the assembly of the battery stack to avoid dimensional changes caused by swelling of the ion membrane, increase the difficulty of battery stack assembly, and reduce the reliability of the battery stack.
[0003] The defects or problems of the existing technology are as follows:
[0004] 1. Due to its physical properties, the ion membrane swells after contact with water or solution, causing the membrane size to change, which brings inconvenience to the drilling and assembly processes;
[0005] 2. When the swollen ion membrane comes into contact with other solutions, the swelling rate will change again due to different solution concentrations. Therefore, when the flow battery is running, the ion membrane inside the battery comes into contact with the electrolyte, and the membrane size will change again. The membrane is fixed all around, so the ion membrane inside the battery is in a tight state, which has the risk of rupture and causes internal leakage of the battery.
[0006] 3. All-vanadium liquid flow battery separators usually use cationic membranes. During charge and discharge, hydrogen ions are exchanged in the form of hydrated ions. However, hydrated vanadium ions also permeate the membrane under the action of concentration difference osmosis. The poor vanadium barrier performance causes battery capacity loss and low battery coulombic efficiency.
[0007] Previous ion membrane pretreatment methods can only temporarily improve the coulombic efficiency of the battery, but the cycle stability is very poor, and the performance decays rapidly during long-term charge and discharge operation. Summary of the invention
[0008] In view of the drawbacks of the prior art, the present invention provides a method for pretreatment of an ion membrane of a flow battery to effectively solve the technical problems mentioned in the background technology.
[0009] The above object of the present invention is achieved through the following technical solutions:
[0010] A method for pretreating an ion membrane of a flow battery comprises the following steps in sequence:
[0011] Step (1), immersing the ion membrane in a primary treatment solution for not less than 24 hours at room temperature, taking it out, washing the residual solution on the membrane surface with deionized water, and drying it naturally;
[0012] Step (2), immersing the ion membrane treated in step (1) into a secondary treatment solution for 2-8 hours at room temperature.
[0013] Note: The ion membrane should be kept flat throughout the processing and should not be bent or stacked.
[0014] The components of the primary treatment liquid are one or more of D-glucuronic acid, D-arabinose, and L-rhamnose, and the concentration thereof is 0.01-0.10 g / L;
[0015] The secondary treatment solution is a neutral salt solution of alkali metal ions, and the salt may be one or more of potassium ion sulfate, potassium ion chloride, sodium ion sulfate, and sodium ion chloride, and the solution concentration is 0.1-2.0 mol / L;
[0016] The deionized water conductivity is lower than 10 μS / cm;
[0017] The room temperature should be 15-25°C;
[0018] The ion membrane pretreated by the above method can be directly punched, cut and stored in the secondary treatment solution after the operation. The surface needs to be cleaned with deionized water for 30 seconds before use, and then used for battery assembly.
[0019] The ion membrane material may be any one of a perfluorosulfonic acid membrane, a partially fluorinated membrane, and a non-fluorinated cation exchange membrane with a dry film thickness of 50-80 μm;
[0020] The primary treatment liquid can introduce hydroxyl and carbonyl functional groups into the ion membrane to improve the ion selectivity of the membrane. Due to different hydration degrees of the ions, the forces of the ions and the ion exchange groups on the membrane matrix are different, so the swelling degree of the membrane will also change; the secondary treatment liquid can make the oxygen atoms in the sulfonic acid group coordinate with different numbers of metal ions and water molecules in the metal hydrated ions to form hydrogen bonds, and the method is flexible and modifiable, and the swelling rate of the ion membrane can be controlled; the ion membrane after the above complete treatment has high selectivity and an adjustable swelling rate.
[0021] The beneficial effects of the present invention compared with the prior art are:
[0022] 1. After the ion membrane is treated with the primary treatment solution, the ion selectivity is improved and the battery coulomb efficiency is significantly improved; the ion membrane after the complete secondary treatment has both high ion selectivity and adjustable swelling rate;
[0023] 2. When the battery assembled with the ion membrane after complete secondary treatment is placed in the acidic vanadium energy storage medium, the membrane size hardly changes, which can significantly reduce the risk of internal leakage of the battery stack caused by ion membrane swelling;
[0024] 3. The ion membrane after complete secondary treatment can significantly reduce the vanadium ion mobility between the positive and negative electrodes, improve the vanadium resistance of the membrane, slow down the battery capacity decay, significantly improve the battery charge and discharge efficiency, and reduce power loss;
[0025] 4. After the complete secondary treatment, the ion membrane has stable performance after long-term charge and discharge operation without attenuation, which improves the battery cycle stability and extends the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0027] Attached Figure 1 This is a comparison chart of single battery cycle stability;
[0028] Attached Figure 2 This is a comparison chart of the cycle stability of the battery stack. DETAILED DESCRIPTION
[0029] The present invention is described in detail below by specific examples, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.
[0030] Example 1
[0031] Step (1), selecting a 50 μm thick perfluorosulfonic acid film, removing the surface protective film and keeping it dry;
[0032] Step (2), processing the ion membrane selected in step (1) into samples with a size of 100 mm × 80 mm, in parallel with three groups, ensuring that the dimensional error is within ±1%;
[0033] Step (3), preparing a primary treatment solution with a D-glucuronic acid concentration of 0.01 g / L using deionized water;
[0034] Step (4), using three clean and dry beakers to measure 500 mL of the primary treatment solution prepared in step (3), and immersing the three groups of ion membrane samples prepared in step (2) in the three beakers, respectively, and marking them, and immersing them for 24 hours;
[0035] Step (5), after the soaking is completed, the ion membranes in the three beakers in step (4) are taken out respectively, and the residual solution on the surface is washed off with deionized water, and the sizes of the three groups of ion membrane samples are measured and recorded with a steel ruler with an accuracy of 0.5 mm. After completion, the three groups of samples are stored in three beakers filled with deionized water respectively;
[0036] Step (6), preparing a secondary treatment solution having a sodium chloride concentration of 0.1 mol / L with deionized water;
[0037] Step (7), use three clean, dry beakers to measure 500 mL of the secondary treatment solution prepared in step (6),
[0038] Take out the three groups of samples that have undergone primary treatment in step (5), remove the residual moisture on their surfaces, and place them into three marked beakers for secondary treatment, soaking for 2 hours;
[0039] Step (8), taking out the three groups of samples in step (7), washing them with deionized water for 30 seconds, measuring and recording the sample sizes;
[0040] Step (9), placing the three groups of samples in step (8) in an acidic vanadium energy storage medium and soaking them continuously for more than 50 hours to make their sizes fully stable, taking them out and drying the surface solution, measuring and recording the sample sizes;
[0041] Step (10), assemble the sample measured in step (9) into an electrode with an area of 48 cm 2 One single battery;
[0042] Step (11), performing a single cell performance test on the single cell assembled in step (10) according to the requirements in Table 1, and calculating the cell efficiency.
[0043] Table 1 Single battery system parameters
[0044]
[0045] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after treatment in step (8) is 4.1%, and the vanadium (IV) ion permeability is 0.040 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulombic efficiency during constant current charge and discharge is 98.36%. The swelling rate of the membrane after immersion in step (9) is still 4.1%, indicating that the swelling rate of the ion membrane after complete secondary pretreatment is relatively stable.
[0046] Example 2
[0047] The steps of Example 2 are basically the same as those of Example 1, except that the concentration of D-glucuronic acid in the primary treatment solution prepared in step (3) is 0.05 g / L.
[0048] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 3.9%, and the vanadium (IV) ion permeability is 0.036 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.62% during constant current charge and discharge.
[0049] Example 3
[0050] The steps of Example 3 are basically the same as those of Example 2, except that the concentration of D-glucuronic acid in the primary treatment solution prepared in step (3) is 0.10 g / L.
[0051] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 4.0%, and the vanadium (IV) ion permeability is 0.037 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.57% during constant current charge and discharge.
[0052] It can be seen from Examples 1 to 3 that when the primary treatment liquid component is D-glucuronic acid, the performance of the ion-exchange membrane after pretreatment shows a trend of first increasing and then decreasing as the concentration of the component increases.
[0053] Example 4
[0054] The steps of Example 4 are basically the same as those of Example 1, except that the concentration of sodium chloride in the secondary treatment solution prepared in step (6) is 1.0 mol / L.
[0055] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 3.7%, and the vanadium (IV) ion permeability is 0.032 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.80% during constant current charge and discharge.
[0056] Example 5
[0057] The steps of Example 5 are basically the same as those of Example 4, except that the concentration of sodium chloride in the secondary treatment solution prepared in step (6) is 2.0 mol / L.
[0058] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 3.8%, and the vanadium (IV) ion permeability is 0.036 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.60% during constant current charge and discharge.
[0059] It can be seen from Examples 1, 4 and 5 that when the component of the secondary treatment liquid is sodium chloride, the performance of the ion membrane after pretreatment also shows a trend of first increasing and then decreasing as the concentration of the component increases.
[0060] Example 6
[0061] The steps of Example 6 are basically the same as those of Example 5, except that in step (7), the pretreatment time of the ion membrane in the secondary treatment solution is 5 hours.
[0062] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 3.7%, and the vanadium (IV) ion permeability is 0.036 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.64% during constant current charge and discharge.
[0063] Example 7
[0064] The steps of Example 7 are basically the same as those of Example 6, except that in step (7), the pretreatment time of the ion membrane in the secondary treatment solution is 8 hours.
[0065] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 3.6%, and the vanadium (IV) ion permeability is 0.035 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.65% during constant current charge and discharge.
[0066] It can be seen from Examples 5 to 7 that when the components and concentration of the secondary treatment liquid remain unchanged, the longer the pretreatment time of the ion membrane, the lower the swelling rate and the vanadium (IV) ion permeability, but numerically the degree of this change is very small, indicating that the pretreatment time of the secondary treatment liquid has a relatively slow effect on the ion membrane.
[0067] Example 8
[0068] The steps of Example 8 are basically the same as those of Example 1, except that the component of the secondary treatment solution prepared in step (6) is 0.1 mol / L potassium chloride.
[0069] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 4.0%, and the vanadium (IV) ion permeability is 0.040 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.40% during constant current charge and discharge.
[0070] It can be seen from Example 1 and Example 8 that when the component of the secondary treatment solution is chloride salt of alkali metal ions, at the same molar concentration, the secondary treatment solution has basically the same effect on the swelling rate of the ion membrane and the permeability of vanadium (IV) ions, and the battery performance is also relatively similar.
[0071] Example 9
[0072] The steps of Example 9 are basically the same as those of Example 1, except that the component of the secondary treatment solution prepared in step (6) is 0.1 mol / L sodium sulfate.
[0073] The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 4.2%, and the vanadium (IV) ion permeability is 0.041 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.30% during constant current charge and discharge.
[0074] As can be seen from Example 1 and Example 9, when the component of the secondary treatment liquid is sulfate of alkali metal ions, at the same solution molar concentration, the valence of the counter ions in the treatment liquid system increases, the concentration of the common ions increases, the effect on the swelling rate of the ion membrane decreases, the effect on the vanadium resistance performance is similar, and the battery performance difference is not large, because chloride and sulfate are both strong acid salts, and therefore have similar results. As shown in Examples 1-9: The swelling rate of a 50μm thick perfluorosulfonic acid membrane can be regulated by adjusting the components and concentration of the treatment liquid.
[0075] Example 10
[0076] The steps of Example 10 are basically the same as those of Example 1, except that the thickness of the perfluorosulfonic acid film selected in step (1) is 80 μm.
[0077] The swelling rate of the 80 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 4.0%, and the vanadium (IV) ion permeability is 0.035 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency during constant current charge and discharge is 98.67%. It can be seen that the present invention is also effective for 80 μm thick perfluorosulfonic acid membranes, and the numerical improvement of the vanadium resistance of the ion membrane and the coulomb efficiency of the battery is related to the characteristics of the membrane matrix.
[0078] Embodiment 11
[0079] The steps of Example 11 are basically the same as those of Example 1, except that the object selected in step (1) is a 50 μm thick partially fluorinated membrane. The swelling rate of the 50 μm thick partially fluorinated membrane after complete secondary pretreatment is 3.0%, and the vanadium (IV) ion permeability is 0.034 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.72% during constant current charge and discharge.
[0080] Example 12
[0081] The steps of Example 12 are basically the same as those of Example 1, except that the object selected in step (1) is a 50 μm thick non-fluorine cationic membrane. The swelling rate of the 50 μm thick non-fluorine cationic membrane after complete secondary pretreatment is 4.0%, and the vanadium (IV) ion permeability is 0.028 mmol / L / h / cm 2The coulombic efficiency of a single cell is 99.25% when charged and discharged at a constant current of 80mA / cm2.
[0082] Example 13
[0083] The steps of Example 13 are basically the same as those of Example 1, except that the composition of the primary treatment solution in step (3) is 0.01 g / L D-arabinose. The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 3.9%, and the vanadium (IV) ion permeability is 0.041 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency is 98.28% during constant current charge and discharge.
[0084] Embodiment 14
[0085] The steps of Example 14 are basically the same as those of Example 1, except that the composition of the primary treatment solution in step (3) is 0.01 g / L of L-rhamnose. The swelling rate of the 50 μm thick perfluorosulfonic acid membrane after complete secondary pretreatment is 4.0%, and the vanadium (IV) ion permeability is 0.041 mmol / L / h / cm 2 , single cell at 80mA / cm 2 The coulomb efficiency during constant current charge and discharge is 98.31%.
[0086] It can be seen from Example 1, Example 13 and Example 14 that the change of the components of the primary treatment liquid has a certain influence on the performance of the membrane.
[0087] Embodiment 15
[0088] The steps of Example 15 are basically the same as those of Example 2, except that the component concentration of sodium chloride in step (6) is 1.0 mol / L, and the pretreatment time of the ion membrane in step (7) is 5 hours. A single cell durability test was performed on the pretreated ion membrane according to the above steps, and the results are as follows.
[0089] Table 2 Three major efficiencies of single battery
[0090]
[0091] After the above steps, the swelling rate of the ion membrane was 3.7%, and the vanadium (IV) ion permeability was 0.029mmol / L / h / cm 2 , single cell at 80mA / cm 2 The initial coulomb efficiency is 99.22% during constant current charge and discharge. It can be seen that the ion selectivity of the ion membrane after secondary pretreatment is significantly improved, the vanadium resistance is good, the coulomb efficiency is significantly improved, and the performance has no obvious attenuation after long-term stable charge and discharge operation. The battery has high stability and good reliability.
[0092] Example 16
[0093] Example 16 is basically the same as the first 9 steps of Example 15, except that the ion membrane selected in step (1) is a 50 μm partially fluorinated membrane, and the experiment is carried out according to Table 3 starting from step (10), and the voltage range of the stack charge and discharge test is consistent with the single cell test window.
[0094] Table 3 Stack parameters and test conditions
[0095]
[0096] After the above steps, the swelling rate of the partially fluorinated ion membrane was 2.8%, and the vanadium (IV) ion permeability was 0.030 mmol / L / h / cm 2 , the test results of the battery stack charge and discharge performance are as follows:
[0097] Table 4 Initial performance of the battery stack
[0098]
[0099] It can be seen from the above experiments that the initial performance of the battery stack assembled with the ion membrane that has been treated twice is significantly improved, indicating that the ion membrane has high selectivity and good vanadium resistance. In addition, the performance of the battery stack after long-term operation is basically stable, indicating that the ion membrane has good stability and high reliability. After the battery stack is assembled with the ion membrane that has been pretreated by the present invention, the incidence of internal leakage in the battery stack is greatly reduced, indicating that the regulation of the swelling rate of the ion membrane determines the reliability of the battery stack to a large extent.
[0100] Comparative Example 1
[0101] In Example 1, Example 10, Example 11 and Example 12, 50 μm and 80 μm thick perfluorosulfonic acid membranes, 50 μm thick partially fluorinated membranes and 50 μm thick non-fluorinated cationic membranes were pretreated under the same conditions respectively. The performance of the untreated original membranes is not reflected in the example results and is now compared with the examples, as shown in Table 5.
[0102] Table 5 Performance comparison between original membrane and pretreated membrane
[0103]
[0104] The above comparison shows that the material properties of the ion membrane make it show different physical and chemical properties. For the same material ion membrane, its thickness also has a relatively large impact on the physical properties. From the results, it can be seen that the ion membrane after secondary pretreatment has achieved controllable swelling rate, significantly improved ion selectivity, and improved battery charge and discharge performance.
[0105] Comparative Example 2
[0106] Examples 5 to 7 demonstrate that when the components and concentration of the secondary treatment solution remain unchanged, the swelling rate of the ion membrane and the vanadium (IV) ion permeability slowly decrease as the membrane is pretreated in the secondary treatment solution for an increasing period of time. In this example, the performance changes of the ion membrane after 11 hours of secondary treatment are compared.
[0107] Table 6 Comparison of ion membrane performance
[0108]
[0109] From the above comparison, it can be seen that the longer the pretreatment time of the ion membrane in the secondary treatment liquid, the better. Otherwise, it will have a negative impact on the performance of the membrane and may accelerate the denaturation and aging of the ion membrane.
[0110] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.
Claims
1. A method for pretreatment of ion membrane in a flow battery, characterized in that: The following steps are included in sequence: Step (1), immersing the ion membrane in a primary treatment solution for a period of not less than 24 hours at room temperature, washing the residual solution on the membrane surface with deionized water after taking it out, and drying it naturally; the ion membrane material is any one of a perfluorosulfonic acid membrane, a partially fluorinated membrane, and a non-fluorinated cation exchange membrane; the component of the primary treatment solution is one or more of D-glucuronic acid, D-arabinose, and L-rhamnose; Step (2), immersing the ion membrane treated in step (1) into a secondary treatment liquid, a neutral salt solution of alkali metal ions, at room temperature for 2-8 hours.
2. A method for pretreatment of an ion membrane of a flow battery according to claim 1, characterized in that: The concentration of the primary treatment solution is 0.01-0.10 g / L.
3. A method for pretreatment of an ion membrane of a flow battery according to claim 1, characterized in that: The salt of the neutral salt solution of alkali metal ions is one or more of sulfate of potassium ions, chloride of potassium ions, sulfate of sodium ions, and chloride of sodium ions.
4. A method for pretreatment of an ion membrane of a flow battery according to claim 1, characterized in that: The concentration of the alkali metal ion neutral salt solution is 0.1-2.0 mol / L.
5. The method for pretreatment of ion membrane of a flow battery according to claim 1, characterized in that: The deionized water conductivity is less than 10 µS / cm.
6. A method for pretreatment of ion membrane in a flow battery according to claim 1, characterized in that: The room temperature should be 15-25°C.
7. A method for pretreatment of ion membrane in a flow battery according to claim 1, characterized in that: The dry film thickness of the ion membrane material is between 50-80 μm.
Citation Information
Patent Citations
Composite electrode material and preparation method thereof, and applications of composite electrode material in all-vanadium flow battery
CN106549162A
Composite membranes for redox flow battery electrolyte and their fabrication method
KR1020160064429A